Pengaruh Kepemimpinan Transformasional Dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Balai Besar Meteorologi Klimatologi Dan Geofisika (Bbmkg) Wilayah II Tangerang Selatan - Mu’minah Mu’minah; Raden Yeti Sumiaty (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The purpose of this study was to determine the effect of Transformational Leadership and Work Discipline on Employee Performance at the Meteorology, Climatology and Geophysics Center (BBMKG) Region II South Tangerang both partially and simultaneously. The method used is the Quantitative method. The sampling technique used is saturated sampling with a sample of 80 respondents. Data analysis using validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this study are that transformational leadership has a significant effect on Employee Performance partially, indicated by a simple linear regression equation Y = 7.710 + 0.833X1. This is proven by the hypothesis test obtained t count> t table (16.349> 1.990) and strengthened ρ value <Sig.0.05 or significance <0.05 (0.000 <0.05). Work Discipline has a significant effect on Employee Performance partially indicated by a simple linear regression equation Y = 9.820 + 0.776X2. This is proven by the hypothesis test obtained a calculated value of t> ttable (15.242 > 1.990) and strengthened by a ρ value < Sig.0.05 or significance < 0.05 (0.000 < 0.05). The results of the study Transformational Leadership and Work Discipline simultaneously have a significant effect on Employee Performance in (BBMKG) Region II South Tangerang are shown by a multiple linear regression equation Y = 5.108 + 0.494X1-0.402X2. This is proven by the results of the hypothesis test simultaneously obtained a calculated F value> F table (211.175 > 3.110) and strengthened by a significance value < 0.05 (0.000 < 0.05). The results of the coefficient determination test of the Transformational Leadership and Work Discipline variables have an influence of 84.6% on Employee performance in (BBMKG) Region II South Tangerang. Thus, H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between Transformational Leadership (X1) and Work Discipline (X2) on Employee performance (Y).